Written Composition and Quality of the Argumentative Text from Self-regulated Mediation - Gotopo, Navas Soratna (2022)
This work discloses the results of an investigation whose objective was to determine the incidences of self-regulation in the process of writing argumentative texts in university students. The sample consisted of 20 students, aged between 16 and 18 years, drawn from a conglomerate of 40 students from the first cycle of the CRT1 course. The analysis of the information confirmed, regarding the process of written composition, that the students did not fully apply the underlying cognitive skills in such process, while writing was perceived as an academic event, whose recipient was always the teacher. Regarding the text prepared by the students, deficiencies were observed regarding the argumentative superstructure, text properties and writing regulations. After the mediation, with a learning project from a strategic teaching approach, there were considerable advances with respect to the initial situation -pretest; This proved that self-regulation positively affects both the written composition of argumentative texts and the quality of the texts produced by students. In addition, it was found that indicators of self-regulated learning underlie written composition.